COOPERATION PROBLEMS OF THE STATE AND BUSINESS IN THE FIGHT AGAINST THE SHADOW ECONOMY AND CORRUPTION - R. Akalovich (Вестник университета)
In the article there are marked difficulty fighting corruption in government agencies, are considered the interests of business structures in the implementation of anti-corruption policy. The characteristic of the shadow capital of corrupt subjects of public relations as a factor of occurrence of unequal conditions in the market is done. The positive and negative points of possible participation of commercial entities in anti-corruption activities of the state are analyzed. Proposals to empower the business community with additional authorities that can help reduce the level of corruption are done.